The Application of Project Base Constructive Paly to Encourage Student's Ability in Creative Expression and Communication - Helmi, Moch; Nurihsan, Juntika; Saud, Udin Syaefudin (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2015)
This research is conducted based on several findings in TK Sejahtera, Bandung regarding to its teaching practice and the nature of the children progress. The application of quasi experiment on the project base play program is aimed to redirect children desire to play and aggressive energy into schemed creative activity. Children mostly show their preference as adaptive problem solver in their creative style and always try to negotiate their idea in communication process. The outcome of the research shows some progress in children creative and communication abilities in the test of variance. The experiment shows large effect in creative expression medium significance in communication ability. It can be conclude that the research have successful in endorsing children creative and communication ability along with their various characteristics